The interaction between the traditional and new musical language in folk and author’s songs under the Tuvan People’s Republic - Baranmaa, Ayasmaa D.-B. (The New Research of Tuva, 2020)
The article examines folk and author’s songs which appeared during the years of the Tuvan People’s Republic, in the perspective of introducing the European major/minor scale into the traditional Tuvan music, which can be classified as belonging to anhemitonic/pentatonic scale system. It were the early 20th century composers (rather than creators of folk music) who first made use of the heptatonic scales of major and minor in Tuvan music. Methodologically, our research is based on the principles of comprehensive analysis in Russian music studies, which takes into account a whole range of factors in musical expression.New song lyrics were created for the well-known melodies of the kozhamyk (ditties) and kyska yr (short songs), both of which are known for rhythmical clarity and constancy. During the period we focus on, the range of melodies in use expanded dramatically, with new melodic turns gaining traction and non-standard ones coming into use. A special focus is made on the “Kaygamchyktyg Internatsional” (Marvellous International) – a striking example of traditional musical folklore.The article examines the heritage of M. Munzuk, V. Kok-ool and A. Laptan – composers who combined the use of traditional songs with elements of new genres (the march, anthem and waltz), with the whole range of rhythms, and major and minor keys typical; for them.
Keywords: Tuvan People’s Republic; Tuvan music; history of Tuva; song folklore; Tuvan folklore; folk song; author’s songs; traditional music; composers’ art; monody; anheitonics